Former Drug Addicts Quality of Life: A Qualitative Study - Huwae, Arthur; Rugebregt, Joanne Marrijda; Mage, Mernon Yerlinda Carlista; Rondonuwu, Hizkia Caesaryo Pehala (Kuras Institute, 2025)
Living life as a former drug addict poses significant challenges. Holistically, the impact felt will be very heavy to live. However, life goes on and as a former drug addict is required to improve bad life into a healthy and better quality. The purpose of this study is to explore the description of quality of life in former drug addicts. The method used was qualitative with a descriptive phenomenological design. The participants involved were 3 former drug addicts using purposive sampling technique. The results showed that quality of life physically, psychologically, socially, and environmentally varied in meaning by the three participants. Although, the three participants continue to learn to improve their lives, there is no denying that there are still internal judgments that are expressed about their existence as former drug addicts. Furthermore, the process of improving themselves and their lives continues to be carried out by the three participants by continuing to try positive things to realize a life that has a positive impact on themselves and the environment, in order to achieve quality of life in totality. Social support is important from family, friends, and close people to former addicts, so that they can see opportunities for self-esteem. Future studies should explore social interventions to educate communities on providing holistic support to former drug addicts to overcome the challenges of reintegration.